The Articulation of Local Government Financial Statements and Their Effect on Its Quality - Bella Meihana; Abdul Halim; Evi Maria (The Indonesian Journal of Accounting Research, 2021)
This research aims to analyze the level of articulation of Local Government Financial Statement (LKPD) and their effects on the quality of LKPD as a basis for local government economic decision making. Data sources used in this research are secondary data and primary data. Secondary data consisting of LKPD documents with Unqualified Opinion. These documents were obtained from the Indonesian Supreme Audit Institutions’s (BPK) Financial Audit Report (LHP) in 2018. Secondary data analysis is carried out using content analysis techniques. The analysis is carried out by comparing the numbers of LKPD based on the set of articulation criteria that were built based on Government Accounting Standards (SAP) and previous research. Primary data consist of semi-structured interviews with local governments which have an articulation rate of less than 100%. Analysis of primary data from interviews is using the Miles and Huberman’s model. Based on the analysis of 443 LKPD documents, it was found that 131 or 30% LKPD had an articulation rate of 100% and 312 or 70% LKPD had an articulation rate of less than 100%. The average level of articulation of LKPD in Indonesia is 83% with the lowest articulation rate of 54%. Based on the results of interview, show that articulation affects the quality of financial statement and influences economic decisions in the the budget preparation process with the function of LKPD as a comparison and prediction tool.